OBSERVATION ON THE FISHERY AND BIOLOGY OF PENAEID PRAWNS FROM GODAVARI ESTUARY - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
The Godavari estuarine system ofAndhra Pradesh covering an area of 330sq. km, supports a lucrative prawn fishery.Subrahmanyam (1965, 1967, 1973) andGanapati and Subrahmanyam (1966)made preliminary study of the prawnfishery of this area. Rao (1975) dealtwith the prawn fishery of the Kakinadabackwaters based on the data collectedfrom Boddu Venkatayapalem during1968-73.